Were policies in Brazil effective to reducing trans fat from industrial origin in foods? - Flávia da Silva Lima Dias; Mário Ferreira Lima; Patricia Coelho de Velasco; Rosana Salles-Costa; Fátima Lúcia de Carvalho Sardinha; Maria das Graças Tavares do Carmo (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To determine the trans fatty acids content of processed foods frequently consumed by adults living in a Rio de Janeiro, Brazil, after the enactment of a mandatory trans fatty acids labelling policy. METHODS Between February 2014 and January 2015, a specifically dietary questionnaire was completed by 107 adults to assess the frequency of processed foods consumption. The most commonly consumed products from the survey, including vegetable oils, margarine, biscuits, snacks, cheese bread (pão de queijo), french fries, cheeseburger and ice cream, were then analyzed for their trans fatty acids content using gas chromatography with a flame ionization detector. RESULTS Differences in the levels of trans fatty acids were observed among 22 products analyzed, considering that trans fatty acids content ranged between 0.0 g/100 g in samples of cream cracker biscuit 1 and olive oil to 0.83 g/100 g in samples of cheeseburger (fast food), 0.51 g/100 g in samples of frozen pão de queijo and 12.92 g/100 g in samples of chocolate sandwich cookies with cream filling 2. The overall trans fatty acids content of the different samples of margarine brands was 0.20 g/100 g for brand 1 and 0.0 g/100 g for brand 2. These data are significantly lower than those observed in a survey conducted in 2003, when the regulation had been enacted. CONCLUSIONS Our data indicate that Brazilian regulation is very likely implicated in the observed drop in trans fatty acids of the most processed foods but has yet to eliminate them, which reinforces the urgent need to revise the legislation, since a minimum amount of trans fat does not mean that the food product does not contain this type of fat.